Investigating the Technological Pedagogical Content Knowledge (TPACK) of EFL Teachers Based on School Status and Teachers Status at SMA/MA of Pangkep Regency - Achmad Sochabat; Ambo Dalle; Zulfah Fakhruddin; Saepudin; Mujahidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to describe the understanding and implementation of TPACK (Technological Pedagogical Content Knowledge) among English teachers in high schools in Pangkep District, focusing on differences based on teacher status and school status. TPACK is a framework that integrates three main components: content knowledge, pedagogical knowledge, and technological knowledge, which are essential for teachers to effectively teach in the digital era. This study uses a quantitative approach with a survey design, involving 58 English teachers from various high schools and madrasahs (Islamic schools) in Pangkep District as a sample, consisting of 34 public schools and 10 private schools. Data were collected using a questionnaire that measures the TPACK dimensions, as well as information regarding teacher status (certified and non-certified) and school status (public or private). The analysis results show that there is no significant difference in TPACK understanding between certified and non-certified teachers, with a significance value of 0.462 > 0.05. Additionally, the school status also does not significantly influence the optimal implementation of TPACK in the learning process, with an average significance value of 0.971 > 0.05. These findings are expected to provide recommendations for educational policy and professional development programs for English teachers in the region to enhance technology-based learning quality.